Regional Financing for Sustainable Development: An Analysis of Successful Practices in Region Stockholm - Rumyantseva , Anna Yu.; Tcerkasevich , Larisa V.; Ivleva , Elena S. (Economy of Regions, 2025)
The implementation of the United Nations’ Sustainable Development Goals (SDGs) requires effective mechanisms to ensure progress, particularly in the face of global challenges. In this context, the successful experience of promoting sustainable development in Region Stockholm, despite budget deficits and challenges in tax collection, is of particular interest. Through an analysis of historical and legal documents, this paper traces the evolution of the concepts and principles guiding regional development in Sweden, demonstrating how the gradual adaptation of the SDGs has incorporated European Union practices. The study of official documentary sources, including budgetary and audit reports, examines key development indicators in Region Stockholm, corresponding budget allocations, and the dynamics of SDG indicators for 2022, 2023, and 2024. The findings highlight financial challenges, including high inflation, weakened budget revenues during the pandemic, and an unplanned increase in pension fund contributions due to a sharp rise in the number of retirees. This paper proposes a methodology for calculating an integral coefficient of regional development sustainability. The methodology involves assessing changes in various development indicators for 2023 relative to 2022. The results indicate that despite financing difficulties and a budget deficit of the region’s revenues amounting to 29 %, most of the planned SDGs were achieved. The overall trajectory of regional development remains positive. The insights gained from Region Stockholm’s experience in advancing the SDGs, strengthening regional budgets, and ensuring effective governance structures can be valuable for strategic management planning in other regions.